Penerapan Model Pembelajaran Kooperatif Tipe Mind Mapping Untuk Meningkatkan Hasil Belajar Siswa Kelas XI IPA 1 SMA Negeri 6 Banjarmasin Pada Pokok Bahasan Usaha Dan Energi - Dian Puspitasari; Zainuddin Zainuddin; Mustika Wati (Universitas Lambung Mangkurat, 2015)
The low result of student learning is caused by teacher centered learning methods. Be required a model of learning which makes to improve the result of student learning. Therefore, be done a research by the implementation of cooperative learning model mind mapping type to improve the result of student learning at XI IPA 1 grade in SMA Negeri 6 Banjarmasin in subject work and energy. The specific aims of the research describe: (1) the lesson plan adherence of cooperative learning model mind mapping type; (2) the result of student learning; (3) the student’s activities; (4) the student’s responses toward learning. The type of the research is a classroom action research of Kemmis & Mc Tagart model which includes planning, observation, and reflection. The technique of data collecting used observations, tests, questionnaires and documentations. The technique of data analysis is qualitative descriptive and quantitative descriptive. The Results of the research showed (1) the lesson plan adherence categorized very well; (2) the result of student learning althought the individual and classical are completeness; (3) the student’s activities categorized very well; (4) the student’s responses categorized well. Be obtained the conclusion that the implementation of cooperative learning model mind mapping type is effective to improve the result of student learning at XI IPA 1 grade in SMA Negeri 6 Banjarmasin in subject work and energy.